PROTECTING SPEECH INFORMATION USING ACTIVE SOUND CANCELING SYSTEMS - Lizunov, Sergey; Filobok, Evgenij (Ukrainian Information Security Research Journal, 2021)
Usually, to eliminate the leakage of information through the acoustic channel, either sound insulation or generators of correlated acoustic noise are used. In the first case (passive method) requires a significant amount of time to carry out sound insulation work. In the second case the presence of noise generators creates discomfort during negotiations. The radiation itself is an unmasking sign, which makes it easier for attackers to determine the time and place of negotiations. The disadvantages of both of the above methods can be reduced by using active noise reduction systems (Active Noise Control, Active Noise Cancellation, ANC, Active Noise Reduction, ANR). Such active noise reduction systems are based on the process of wave interference. Despite the fact that the method itself allows you to effectively suppress ambient sounds, real devices do not always cope with this task, especially with acoustic vibrations with a frequency of more than a thousand Hertz. The fact is that it takes some time for the microcontroller to register the sound and calculate the opposite wave. Because of this, the sound it produces is no longer completely opposite to the incoming sound, but lags behind it in phase. This disadvantage can be reduced if the signal to be suppressed is applied to the input of such a device via an electrical or electromagnetic channel. Due to the fact that the electrical signal spreads faster than sound, the device starts to process the signal even before it comes in the form of an acoustic wave. The noise reduction of such systems works for sounds with a frequency of up to 4 kHz, which is quite acceptable for the spectrum of speech information. Thus, at the boundaries of the controlled area, it is possible to reduce the level of acoustic waves from the sources of confidential information to a safe value. Such systems can be successfully used in secure rooms, where the circulation of acoustic (speech) information is generally prohibited.